CIRC Berbantuan LKM Pohon Literasi Upaya Meningkatkan Sikap Kolaborasi dan Keterampilan Membaca Kata Sulit Kelas IV - Khomsiyati, Ni'matul; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Difficult vocabulary comprehension remains a significant barrier in reading literacy instruction at the elementary level, thereby requiring an instructional model that can simultaneously enhance vocabulary comprehension and students’ collaborative attitudes. This study aimed to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model combined with the student worksheet Pohon Literasi (Literacy Tree) in improving difficult vocabulary comprehension and collaborative attitudes among fourth-grade students at SDN 4 Petarukan. The study employed a one-group pretest–posttest design involving 20 students, with data collected through a difficult vocabulary comprehension test and a collaboration observation sheet. The results indicated a significant improvement in reading ability, as reflected in the increase in mean scores from 61.2 at pretest to 85.2 at posttest, along with an increase in learning mastery from 50% to 85%. The N-Gain analysis yielded a score of 0.62, indicating a medium level of improvement, while all students demonstrated collaborative attitudes in the Good to Very Good categories, suggesting that the implementation of CIRC fostered constructive interaction and cooperation within groups. Based on these findings, it can be concluded that the application of the CIRC model in conjunction with the Pohon Literasi media is effective in enhancing students’ comprehension of difficult vocabulary while simultaneously strengthening their collaborative attitudes, and thus can be recommended as a relevant and practical literacy instruction strategy in elementary schools.